Latin America and the Caribbean Refinery Sector Development Project - Clients - World Bank (Washington, DC, 2014)
This report summarizes two years of intense activity dedicated to the study of the issues confronted by the refining industry in Latin America and the Caribbean. Following the program for phasing out of lead from gasoline and convinced of the importance to progress with the harmonization of oil product's technical specifications, the organizations--OLADE, ARPEL, and the World Bank--decided to jointly carry out a regional study on the refining sector, its anticipated changes, capital requirements, and related financial needs. For the next two or three decades, all projections of energy consumption confirm that liquid fuels will meet most of the energy demand of the transport and commercial sectors. The region's refineries will have to respond to a growing demand for cleaner products, essential to fuel modern engines and preserve air quality. As well, supported by large reserves, natural gas will continue penetrating the electricity and industrial sectors in Latin America. The configuration of the refineries should also conform to this trend. Developing a competitive refining industry is of critical importance to the regional integration process. Despite the current difficulties, economic growth and intra-regional trade in Latin America will continue to expand. To survive many refining companies should have to evolve from supplying in exclusivity national markets to competing in the increasingly open regional market.